Contextualising simulation in emergency medicine department and pediatric intensive care unit in India - Sujatha Thyagarajan; Asit Misra (Wolters Kluwer Medknow Publications, 2016)
Emergency Department and Pediatric intensive care units are acute Pediatric care areas with high risk and require quality and safe care to deliver good outcomes to children. Simulation appears to be adapted well in many Emergency Departments as well as PICUs across the world to understand and optimise the delivery of acute care. We have little data on the adaptability and application of simulation methods into acute Pediatric care provision in India. Simulation is currently limited to a few task-training workshops and is yet to become an integral part of healthcare in day-to-day practice. There is a lot of room to expand the scope of simulation in Emergency Departments and PICUs across the country. There is a need to expand the expertise and numbers of simulation trainers to facilitate the wider application. Further studies are needed to understand the impact on patient outcomes and understand the challenges in wider application to patient care.